The relationship between sleep quality, neck pain, shoulder pain and disability, physical activity, and health perception among middle-aged women: a cross-sectional study - Myung Kyung Lee; Jihyun Oh (BMC, 2022)
Abstract Background Sleep quality is an important physical requirement for a healthy life, and good sleep quality has been recognized as a significant component in physical and mental health and well-being. The purpose of this study was to identify the factors that affect sleep quality as well as the relationship between sleep quality and neck pain, shoulder pain and disability, physical activity, and health perception. Methods We conducted surveys on 494 women between the age of 35 and 64 years. The study evaluated neck pain, shoulder pain and disability, physical activity, self-health perception and sleep quality with self-reported questionnaires in middle-aged women. Data were analyzed using SPSS 23.0. Results The results showed that the more severe the neck pain and shoulder pain and disability, the worse the sleep quality was in middle-aged women and the better the health perception, the lower the sleep quality score was, indicating good sleep quality. Shoulder pain, self-perceived task difficulty, and health perception were identified as variables that affected the sleep quality in middle-aged women. The explanatory power of the model in explaining sleep quality was 22.9%. Conclusions Worsened shoulder pain, self-perceived task difficulty, and negative health perception can affect poor sleep quality; therefore, it is necessary to develop health interventions for pain management and emotional and social support for improving daily sleep quality. To improve the sleep quality in middle-aged women, healthcare workers should consider the subjects' pain and functional disability, in accordance with their health perception.